The EFFECT OF WORK-LIFE BALANCE AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT PLTU BANTEN 1 - Anisah, Deby; Pancasasti, Ranthy; Qolbi, Raihan; Bue Marisa, Sakti (Management Science Research Journal, 2022)
The purpose of this study is to analyze a model that is expected to improve employee performance involving Work-Life Balance and Work Environment. The research method is quantitative using a 10- point ordinal scale questionnaire with a sampling technique carried out by simple random sampling. The number of samples used is 125 people to test (2) the hypothesis that the Structural Equation Model- Partial Least Square (SEM-PLS) model is used to test the statistical significance of the path coefficients. The findings of the study explain that work-life balance has a positive and significant effect on employee performance. The work environment has a positive and significant effect on employee performance